Social capital and innovation of SME's in Harare province Zimbabwe - Mutendadzamera, Kudzanai (My University, 2019)
The objective of this paper was to determine whether the relationship between social capital and organisational innovation is positively moderated by environmental hostility and dynamism. The literature reviewed supports the assertion that non-traditional explanatory variables for innovation are needed as human and social capital are under-researched knowledge resources. As such, three separate sources of social capital were examined: reputational capital, alliance ties and political capital. Organisational innovation as a form of innovation also forms a valuable output variable that deserves greater study. Its use here with social capital advances a challenge found in literature to better understand the elements that contribute to organisational advantage. The question of how these variables manifest in an emerging economy context such as Zimbabwe was unanswered in literature. Adopting dynamism and hostility as moderating variables allowed the empirical assessment of the conditions under which firms in this environment operate. Based on survey data collected and analysed between November and December 2018 in Harare province, support was found for the positive influence of alliance capital on organisational innovation when moderated by hostility and dynamism. Findings did not support the same proposition for political capital and reputational capital.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation
Keywords: Social capital (Sociology); Economic development--Social aspects--Zimbabwe